Seaweeds of Pulau Payar, West Coast Peninsular Malaysia - Ching, Lee W. (Fisheries Research Institute, 2014)
A seaweed survey was conducted around the Pulau Payar Marine Park from 28 to 29 December 1997. This was a joint research project between the University of Malaya and Hokkaido University to study the systematics of Malaysian marine algae. Samples were collected for taxonomic studies and deposited in the herbaria at the University of Malaya and Hokkaido University. A total of four species of Chlorophyta, four species of Rhodophyta and three species of Phaeophyta are reported. Three new records were found.